Hydrops fetalis associated with anti‐CD36 antibodies in fetal and neonatal alloimmune thrombocytopenia: Possible underlying mechanism. Issue 5 (27th July 2020) - Wu, Yongbin; Chen, Dawei; Xu, Xiuzhang; Mai, Mingqin; Ye, Xin; Li, Chengyao; Santoso, Sentot; Xia, Wenjie; Fu, Yongshui
Abstract: Objectives: In the present study, we asked whether anti‐CD36 antibodies impair the maturation of erythropoietic stem cells to mature red blood cells (RBCs), leading to anaemia and hydrops fetalis (HF). Background: Recent studies have shown the importance of anti‐CD36 antibodies in the development of Fetal/Neonatal Alloimmune Thrombocytopenia (FNAIT). In comparison to other types of antibody‐mediated FNAIT, anti‐CD36 antibodies are frequently associated with anaemia and HF. As mature RBCs do not express CD36, the reason for this phenomenon is currently not fully understood. Material and methods: A case of FNAIT with signs of HF was characterised in this study. Maternal anti‐CD36 antibodies were isolated by an absorption/elution approach. We cultured haematopoietic stem cells (HSCs) with purified anti‐CD36 antibodies, and the formation of burst‐forming unit‐erythroid and colony‐forming unit‐erythroid (CFU‐E/BFU‐E) cells was analysed. Apoptosis of HSCs was also investigated. Results: Analysis of the mother showed type‐1 CD36 deficiency. Anti‐CD36 antibodies were found in maternal serum, as well as on fetal platelets, by ELISA, and the specificity of these antibodies was further substantiated by flow cytometry. In comparison to control IgG, incubation of HSCs with purified anti‐CD36 antibodies led to a significant reduction in CFU‐E/BFU‐E cell formation, and this result was associated with an increased number of apoptotic CD34+ erythroid/myeloid precursor cells. Administration of intra‐uterine transfusion with washed RBCs was effective in improving fetal anaemia. Conclusions: Anti‐CD36 antibodies may cause anaemia and trigger HF through apoptosis of CD34+ erythroid/myeloid precursor cells. However, the contribution of other cells must also be taken into account.